STRUKTUR DAN VEGETASI TUMBUHAN BAWAH PADA TEGAKAN PINUS DI RPH KALIRAJUT DAN RPH BATURRADEN BANYUMAS - Nadi Destaranti; Sulistyani Sulistyani; Edy Yani (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
A study on the undergrowth vegetation within the pine woods (Pinus merkusii) stands conducted in RPH Kalirajut and RPH Baturraden. This study aimed to find out the composition of the shrubs of the pine woods stands on those two sites with different altitude and to figure out the similarity of the herbs of the pine woods stands on those two locations with the different height. This study applied quadrat sampling technique, using 30 units of 2 x 2 m quadrats divided into ten sub–transects along the main transect. We measured environmental factors including elevation, temperature, light intensity, and pH of the soil. We found undergrowth vegetation in RPH Kalirajut comprised of 32 species belonging to 20 families, dominated by Ottochloa nodosa, Oplismenus compositus, and Cynodon dactylon. On the other site, we found undergrowth vegetation in RPH Baturraden composed of 19 species belonging to 20 families and dominated by Wedelia trilobata, Paspalum conjugatum, and Clidemia hirta. The similarity of the herbs vegetation measured of those two sites was 30.85% or 69.15% different.